MODELLING AND VERIFICATION OF KITSAT PACKET COMMUNICATION PROTOCOLS - Young-Ro Lee; Dan Keun Sung (Journal of Astronomy and Space Sciences, 1996)
In this paper, in order to verify KITSAT 1/2 packet communication protocols, we model the AX.25 protocol and PACSAT protocol by using an extended Petri net and then verify the correctness, boundedness, liveness and deadlock freeness of packet protocols by utilizing reachability trees.